Flexural characteristics of D-gun sprayed functionally graded alumina and alumina-zirconia ceramic composites coatings. (13th September 2010) - Rajakumar, Sundaram; Vijayaraghavan, L.; Mayuram, M.M.; Krishnamurthy, R.
Detonation gun (D-gun) sprayed alumina and alumina-zirconia ceramic composite are evaluated as monolayered and functionally graded coatings (FGC). The coated specimens are subjected to three-point bending test to assess their flexural response. From the load deformation characteristic of the ceramic deposits, while alumina as a monolayer (ALM) exhibit high modulus of rupture (MOR). Alumina-zirconia FGC (AZG2) has better flexure properties. Structure property relationship and response of acoustic emission from flexure specimen supplement this observation.